Kepemimpinan Transformasional, Kepuasan Kerja dan Komitmen Organisasi - Susiawan, Susilo; Muhid, Abdul (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
This study aims to examine the relationship between transformationalleadership and job satisfaction and organizational commitment. Subjects wereemployees of the production division of PT. Barata Indonesia (Persero) Gresiktotaling 30 people. Data were obtained using a scale of organizational commitment,scale transformational leadership and job satisfaction scale. Based on the analysis ofdata by multiple regression unknown regression F value = 24.063, p = 0.000 (p<0.001), which indicates that there is a very significant positive relationship betweentransformational leadership and job satisfaction and organizational commitment.Thus, the hypothesis